The immunoglobulin M-Shed acute phase antigen (SAPA)-test for the early diagnosis of congenital Chagas disease in the time of the elimination goal of mother-to-child transmission - Castro-Sesquen Y.E. (2021)
The work was supported by Fondo Nacional de Desarrollo Cientifico, Tecnologico y de Innovacion Tecnologica, FONDECYT, Peru (N084-2016) to Y. E. C.-S.; the National Institutes of Health (R01-AI87776 and D43-TW010074 to R. H. G. and D43 TW007393 to A. G. L.); and InBios International, Inc to R. H. G. through the Johns Hopkins Bloomberg School of Public Health.